Blood Harmane Concentrations in 497 Individuals Relative to Coffee, Cigarettes, and Food Consumption on the Morning of Testing. (23rd March 2011) - Louis, Elan D.; Factor-Litvak, Pam; Gerbin, Marina; Jiang, Wendy; Zheng, Wei
Abstract : Harmane, a potent neurotoxin linked with several neurological disorders, is present in many foods, coffee, and cigarettes. We assessed whether morning food/coffee consumption and smoking were reflected in blood harmane concentrations (BHCs) we obtained in an epidemiologic sample (n = 497 ). Participants who smoked on the morning of phlebotomy had similar logBHCs to those who had not smoked (P = .57 ); there was no correlation between logBHCs and number of cigarettes (P = .59 ). Among the coffee drinkers, there was no correlation between number of cups and logBHCs (P = .98 ). Participants who had eaten on the morning of phlebotomy had similar logBHCs to those who had not (P = .49 ); logBHCs did not correlate with the time latency between last food consumption and phlebotomy (P = .74 ). BHCs in this sample of 500 individuals did not covary with recent smoking, coffee, or food consumption, suggesting that our inability to withhold these exposures on the morning of phlebotomy was not reflected in the BHCs we measured.